Dividendo e crescimento: a contribuição da demografia na economia brasileira entre 1970 e 2010 - Vinícius de Araújo Mendes (2013)
The target of this dissertation is to analyze the demographic contribution to Brazilian economic growth since 1970 to 2010. In demographic literature, demographic dividend occurs when the growth rate of effective producers is higher than the growth rate of effective consumers, as a consequence of decline in fertility rate. Then the period when potential working-age people growth higher than population as a whole create a windows of opportunity for accumulation of physical and human capital. Nevertheless the literature of demographic dividend shows that bad institutions could have contributed negatively to demographic dividend, for example. Change in the growth rate of worked people has an economic impact in the long run, changing the capital deepening path and steady state income per capita. In this paper, we will present the estimates of first demographic dividend, the growth accounting based on the contribution of capital per worker, human capital and productivity in the growth rate of per capita income and, finally, economic account and demographic account together for Brazilian output since 1970 to 2010.